The Ideology of Lifetime Employment and Its Influence on Contemporary Japanese Society - I. P. Lebedeva (Russian Japanology Review)
The article discusses the main directions of influence of the system of lifetime employment on contemporary Japanese society. This system evolved over several decades and became a major form of labor management in large Japanese companies in the late 1960s. However, the real scope of its impact was much broader, as not only middle, but also small companies tried to use to a certain extent its basic elements in order to increase the work motivation of their employees. Due to the fact that the system of lifetime employment was based on the fundamental characteristics of the nation’s culture and psychology, it is not only perceived by workers as reasonable, fair, and corresponding to their ideas of what a company is and how it should be managed, but it also became the foundation on which and around which the system of values and the way of life of several post-war generations of the Japanese were formed. In the early 1990s, the economy and society began to change, calling into question the very existence of the lifetime employment system. However, it has proved to be quite flexible and, thanks to a series of measures taken by Japanese companies, has been able to adapt to the changes that have taken place in the economy and society over the past quarter of a century. These measures include the reduction of employment of regular workers, a change in the wage system designed to make it more adequate to the new conditions, relaxation of the rigid conditions of lifetime employment by introducing a “restricted regular employee” status and a number of others. However, the norms and stereotypes generated by the system are much less mobile and flexible, and it became the cause of a number of painful phenomena in Japanese society. These include the “second-rate” position of non-regular workers (in terms of remuneration, the scope of social security, access to the system of in-house training, and social status), the preservation of gender inequality in employment and in family, the polarization of the Japanese youth by income levels and lifestyle, the fall in the marriage and birth rates, etc. Since shifts in public opinion occur rather slowly, Japan is likely to take quite a long time to resolve the contradictions between the entrenched stereotypes and the requirements of the time.